The development of orthodontic elastomeric ligature with sustained fluoride-releasing for the prevention of white spot lesions: an in vitro feasibility study - Strickland, Kativa; Buschang, Peter; Liu, Ying; Noureldin, Amal; Taylor, Reginald; Kesterke, Matthew; Ma, Chi; Jing, Yan (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectivesDemineralization of enamel is a major challenge during and after fixed orthodontic treatment. Fluoride can strengthen the enamel and reduce the occurrence of white spot lesions (WSLs). Current fluoride-releasing products exhibit a short-term release due to initial burst effect, which severely limits clinical effectiveness. O-rings are orthodontic elastomeric ligatures used to support the attachment of arch-wire to each bracket. This study aimed to develop a simple method to coat the O-rings for long-lasting fluoride release.MethodsCalcium fluoride (CaF2) was coated on the commercial O-rings via a dip and dry method using a coating medium composed of a solution of polycaprolactone (PCL) with CaF2 microcrystals. To optimize the fluoride release, the coating media with different concentrations of PCL (2.5%, 5%, and 10%) solution were applied, and the fluoride release was measured for 7 weeks. The morphology and elemental abundance of the coatings were characterized by energy-dispersive X-ray spectroscopy. The resilience of the modified O-rings was evaluated by a standard tensile program.ResultsA thicker coating with a higher elemental abundance of fluoride was achieved by increasing the PCL concentration in the coating medium. The average fluoride release rates of the 2.5%, 5%, and 10% groups in the seventh week were 0.69 μg F−/ring/day, 6.54 μg F−/ring/day, and 6.97 μg F−/ring/day, respectively. 5% and 10% groups showed long-term and linear release within the therapeutic range, while the 2.5% group fell below the range from the sixth week.ConclusionOur study demonstrated Ca-F O-rings displayed sustained fluoride release under in vitro conditions, indicating potential clinical relevance for reducing WSLs during orthodontic treatment. This work represents an early-stage feasibility study and warrants further validation with larger-scale and in vivo conditions.